Walking on a tightrope: Agency and accountability in practitioner inquiry in New Zealand secondary schools. (July 2020) - Dyson, Lisa
Abstract: Teachers are increasingly engaging in inquiry through questioning, investigating, reflecting, and using data about their own practice and the functions of their departments and schools. The purpose of this study was to explore how inquiry is conceived in the literature and how it was enacted and experienced by New Zealand high school teachers. The literature on inquiry often conveys conflicting advice, competing demands, and contradictory purposes. Using interviews with a purposive sample of educators, this paper suggests that inquiry is a central, yet contested, concept; teachers feel tension when enacting inquiry; and their inquiry processes occasionally slip into accountability. Highlights: The concept of inquiry is central to New Zealand teachers' professional identities. Teachers must balance competing demands and values in their inquiries. Teachers feel tensions and conflicting emotions surrounding their enacted inquiry. External accountability creates more tension in teachers' inquiry practices.